Chapter 4 Cultural Distance and Self-Initiated Expatriates' Willingness to Relocate A Research Agenda - Andresen, Maike (Taylor & Francis, 2020)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book deals with 'Cultural Distance and Self-Initiated Expatriates' Willingness to Relocate: A Research Agenda'. It provides progress by explicitly aiming at the dynamic aspects of careers, including developments over time and the role of life and career stages by adopting a longitudinal life-course perspective. The book examines the evidence for the effect of expatriate experience on their careers and explores some of the factors that impact that. It discusses the role of time in expatriate adjustment, focusing specifically on self-initiated expatriates (SIEs), and contrasting them with assigned expatriates (AEs). The book shares the limited existing literature concerning SIEs in small and medium-sized enterprises compared to other organisational forms. It highlights the gaps in research in this area and sets out a research agenda for scholars in this area.